Multiplanet systems in inviscid discs can avoid forming resonant chains. (25th July 2019) - McNally, Colin P; Nelson, Richard P; Paardekooper, Sijme-Jan
ABSTRACT: Convergent migration involving multiple planets embedded in a viscous protoplanetary disc is expected to produce a chain of planets in mean motion resonances (MMRs), but the multiplanet systems observed by the Kepler spacecraft are generally not in resonance. We demonstrate that under equivalent conditions, where in a viscous disc convergent migration will form a long-term stable system of planets in a chain of MMRs, migration in an inviscid disc often produces a system which is highly dynamically unstable. In particular, if planets are massive enough to significantly perturb the disc surface density and drive vortex formation, the smooth capture of planets into MMRs is disrupted. As planets pile up in close orbits, not protected by resonances, close encounters increase the probability of planet–planet collisions, even while the gas disc is still present. While inviscid discs often produce unstable non-resonant systems, stable, closely packed, non-resonant systems can also be formed. Thus, when examining the expectation for planet migration to produce planetary systems in MMRs, the effective turbulent viscosity of the protoplanetary disc is a key parameter.